Best-practice care pathway for improving management of mastitis and breast abscess. Issue 12 (11th July 2018) - Patani, N; MacAskill, F; Eshelby, S; Omar, A; Kaura, A; Contractor, K; Thiruchelvam, P; Curtis, S; Main, J; Cunningham, D; Hogben, K; Al-Mufti, R; et al.
Abstract: Background: Surgical subspecialization has resulted in mastitis and breast abscesses being managed with unnecessary admission to hospital, prolonged inpatient stay, variable antibiotic prescribing, incision and drainage rather than percutaneous aspiration, and loss to specialist follow-up. The objective was to evaluate a best-practice algorithm with the aim of improving management of mastitis and breast abscesses across a multisite NHS Trust. The focus was on uniformity of antibiotic prescribing, ultrasound assessment, admission rates, length of hospital stay, intervention by aspiration or incision and drainage, and specialist follow-up. Methods: Management was initially evaluated in a retrospective cohort (phase I) and subsequently compared with that in two prospective cohorts after introduction of a breast abscess and mastitis pathway. One prospective cohort was analysed immediately after introduction of the pathway (phase II), and the second was used to assess the sustainability of the quality improvements (phase III). The overall impact of the pathway was assessed by comparing data from phase I with combined data from phases II and III; results from phases II and III were compared to judge sustainability. Results: Fifty-three patients were included in phase I, 61 in phase II and 80 in phase III. The management pathway and referral pro forma improved compliance with antibiotic guidelines from 34 per cent to 58·2 per cent overall (phases II and III) after implementation ( P = 0·003). The improvement was maintained between phases II and III (54 and 61 per cent respectively; P = 0·684). Ultrasound assessment increased from 38 to 77·3 per cent overall ( P < 0·001), in a sustained manner (75 and 79 per cent in phases II and III respectively; P = 0·894). Reductions in rates of incision and drainage (from 8 to 0·7 per cent overall; P = 0·007) were maintained (0 per cent in phase II versus 1 per cent in phase III; P = 0·381). Specialist follow-up improved consistently from 43 to 95·7 per cent overall ( P < 0·001), 92 per cent in phase II and 99 per cent in phase III ( P = 0·120). Rates of hospital admission and median length of stay were not significantly reduced after implementation of the pathway. Conclusion: A standardized approach to mastitis and breast abscess reduced undesirable practice variation, with sustained improvements in process and patient outcomes. Abstract : Outcomes improve